Changes of Motivational Variables in Patients with Multiple Sclerosis in an Exercise Intervention: Associations between Physical Performance and Motivational Determinants - Wiebke Geertz; Anna-Sophie Dechow; Stefan Patra; Christoph Heesen; Stefan M. Gold; Karl-Heinz Schulz (Behavioural Neurology)
Objectives. This study examines the effects of a standardized fitness training on motivational factors such as the intention to be physically active, self-efficacy, perceived barriers, counterstrategies, and exercise specific social support in patients with progressive Multiple Sclerosis (MS) and the relation of these factors to physical performance. Methods. Moderately disabled patients with secondary or primary progressive MS (Expanded Disability Status Scale of 4–6) were randomized to a training group or a waitlist control group. Patients completed on average 20 sessions of training tailored to their individual fitness at baseline over a course of 8–12 weeks. Motivational variables (stage of change according to the transtheoretical model (TTM), self-efficacy, perceived barriers, counterstrategies, and exercise specific social support) were assessed via questionnaires at baseline and follow-up. Results. Forty patients completed the trial. We found significant effects on stages of change p=.016 and self-efficacy p=.014 and a trend in counterstrategies p=.08. Significant correlations between change of physical performance during the exercise training and change in the TTM, perceived barriers, and counterstrategies were detected. Conclusion. This study indicates that tailored individual endurance training could stabilize self-efficacy and increase exercise motivation in patients with progressive MS. Motivational variables were related to the physical performance.